(untitled) (Medico Legal Update, 2021)
Child sexual abuse (CSA) is a serious and widespread problem in India as it is in many parts of the world today. Objective: The aim of this study was assess the knowledge on child sexual abuse among school children at Kattankulathur High School and to associate the knowledge on child sexual abuse among school children at kattankulathur High School with their demographic variables. Method : Quantitative approach and non-experimental descriptive research design was used. The data collection included two parts. Part A: Demographic variables, Part B: A Structured questionnaire to assess knowledgeon child sexual abuse among school children. 180 school childrenwho fulfilled the inclusion criteria were selected as samples using non probability convenient sampling technique. The study was conducted at kattankulathur High School, Kancheepuram dt.. Results: The data were analyzed and interpreted based on the objectives using descriptive and inferential statistics.Among 180 school children 90.6% of them had Moderately adequate Knowledge, 9.4% of them had Inadequate knowledge and None of them had adequate knowledge. The p-values are not significant since they are not less than 0.05 hence we can say that there is no significant association between the demographic variables and the knowledge on Child Sexual Abuse at 5% level. Conclusion: child sexual abuse is an important contributor topsychological and emotional disorders, that some children and adolescents may never overcome.